Evaluation of Mexican poverty reduction policies under the COVID-19 pandemic impacts - Shuying, Gou; Xuedong, Liu (Frontiers in Public Health, 2022)
From 2019 to 2020, the Mexican economy declined for two consecutive years, especially in the last one when it was hit by a decline of 8.4% before the COVID-19 pandemic impacts which was not only one of the worst in the OECD club, but also the deepest economic recession since 1932 in the national history. At the same time, both the number of people in poverty and poverty rate in 2020 have increased compared with those registered in 2018 according to the published official data. Through the analysis, we can find that although the Mexican government has increased the efforts in the implementation of the social relief policies and intensified the scope of beneficiaries since taking office, on the behave of the principal of “for the good of all, first the poor (Por el bien de todos, Primero los pobres). Before the negative impacts caused by the economic recession, neither the general decrease in residents' income could be avoided, nor the number of the low-income people who lost the capacity to afford the cost of those products included in the basic consumption basket has been reduced. Besides, in accordance with the benefits obtained by the distinct household deciles based on the income and expenditure survey published by INEGI, it showed that the implementation of government relief measures has relatively reduced the support for the low-income people and further aggravated the deterioration of poverty due to its indifferent application with respect to high-income households and the low-income ones. Therefore, the deficiencies in the response measures implemented in the face of the epidemic, especially poverty alleviation actions and social relief policies, have further enhanced the poverty problem at least partially. In this sense, recover and improve the economic growth rate as soon as possible will not enough to reduce the poverty, and it should be accompanied by the necessary adjustments in the poverty alleviation measures and social relief policies, especially with a focalized approach inclined to the low-income segments of the population.